Peranan Yayasan Lentera Anak Bali (LAB) Terhadap Pemberdayaan Anak Yang di Eksploitasi di Pasar Badung - I Putu Dony Setiawan; I Nyoman Gede Sugiartha; Luh Putu Suryani (Jurnal Analogi Hukum, 2022)
Exploitation that acts arbitrarily or excessively against the subject of exploitation, regardless of dignity, justice, or equality of welfare, purely for economic gain. The question raised in this paper is how the factors that influence the occurrence of child exploitation affect the Badun market. And what role does the Bali Children's Foundation (LAB) play in the exploitation of children in the Badung market? The purpose of this study is to identify the cause of child exploitation. The survey method used is an empirical survey method. The results of the survey can be explained by the fact that the proportion of children still being exploited has increased or decreased in the last three years. This can be seen in the establishment of the Lanterna Anak Bali Foundation, a dedicated foundation. They take care of children exploited in the Badun market area and the factors that cause the exploitation of environmental impacts, vulnerabilities, and domestic violence of parents in the Badun market area. And the role of the Varilentera Children's Foundation is to provide educational facilities for these children.